Structural regulation and dynamic behaviour of organelles during plant meiosis - Koç, Aybars; De Storme, Nico (Frontiers in Cell and Developmental Biology, 2022)
Eukaryotes use various mechanisms to maintain cell division stability during sporogenesis, and in particular during meiosis to achieve production of haploid spores. In addition to establishing even chromosome segregation in meiosis I and II, it is crucial for cells to establish balanced partitioning of organelles to daughter cells, to properly inherit cellular functions. In plants, cytological studies in model systems have yielded insights into the meiotic behaviour of different organelles, i.e., clearly revealing a distinct organization at different stages throughout meiosis indicating for an active regulatory mechanism. However, how, and why plant meiocytes organize synchronicity of these elements and whether this is conserved across all plant genera is still not fully elucidated. It is generally accepted that the highly programmed intracellular behaviour of organelles during meiosis serves to guarantee balanced cytoplasmic inheritance. However, recent studies also indicate that it contributes to the regulation of key meiotic processes, like MTOC organization and spindle orientation, thus exhibiting different functions than those characterized in mitotic cell division. In this review paper, we will outline the current knowledge on organelle dynamics in plant meiosis and discuss the putative strategies that the plant cell uses to mediate this programmed spatio-temporal organization in order to safeguard balanced separation of organelles. Particular attention is thereby given to the putative molecular mechanisms that underlie this dynamic organelle organization taken into account existing variations in the meiotic cell division program across different plant types. Furthermore, we will elaborate on the structural role of organelles in plant meiosis and discuss on organelle-based cellular mechanisms that contribute to the spatial organization and molecular coordination of key meiotic processes, including spindle positioning, chromosome segregation and cell division. Overall, this review summarizes all relevant insights on the dynamic behaviour and transmission of organelles during plant meiosis and discusses on their functional role in the cellular and molecular regulation of meiotic cell division.